Investment and Resource Use Pattern followed by Dairy Farmers in Haryana (Indian Journal of Extension Education, 2021)
Dairy sector plays a critical role in growth of rural India by providing livelihood opportunities to millions of people. The present study was conducted in Zone-I and Zone II of the Haryana state. District Kaithal and Karnal were selected from Zone I whereas Sirsa and Hisar districts represented Zone II to study the investment and resource use pattern followed by the dairy farmers. To achieve the objective the primary data from the 200 sampled dairy farms (divided into three categories i.e. small, medium and large herd size of milch animals) were collected through survey method. The study revealed that the total investment per milch animal per day in small, medium and large herd size group was Rs.175.50, 178.40 and 181.80, respectively, in Zone-I and Rs.170.08, 174.30 and 175.86, respectively, in Zone-II. From total investment, major proportion was covered by investment on feed and fodder, followed by concentrates and labours in both the Zones. It may be suggested that providing feed concentrates and high yielding seeds of green fodder crops at cheaper rates and credit facility should be strengthened.